Hydrophobic but Water-Friendly: Favorable Water-Perfluoromethyl Interactions Promote Hydration Shell Defects - Robalo, Joao R.; Streacker, Louis M.; De Oliveira, Denilson Mendes; Imhof, Petra; Ben-Amotz, Dor; Verde, Ana Vila (Journal of the American Chemical Society, 2019)
Although perfluorination is known to enhance hydrophobicity and change protein activity, its influence on hydration-shell structure and thermodynamics remains an open question. Here we address that question by combining experimental Raman multivariate curve resolution spectroscopy with theoretical classical simulations and quantum mechanical calculations. Perfluorination of the terminal methyl group of ethanol is found to enhance the disruption of its hydration-shell hydrogen bond network. Our results reveal that this disruption is not due to the associated volume change but rather to the electrostatic stabilization of the water dangling OH···F interaction. Thus, the hydration shell structure of fluorinated methyl groups results from a delicate balance of solute-water interactions that is intrinsically different from that associated with a methyl group.
CRIS-Team Scopus Importer:2020-02-18